Sertifera, a new generic record for the Peruvian orchid flora - Trujillo, Delsy (2018)
An orchid species, previously known from Northern Andes, is reported for rst time in Peru: Sertifera purpurea. A description, illustration, photographs, and comments about the species are provided.